Aritmética modular: uma aplicação no ensino fundamental - Pinheiro, Rodolfo Cavalcante (2018)
This paper presents a proposal to work with Modular Arithmetic with elementary students II (6th, 7th, 8th and 9th years) in order to make the teaching of mathematics more in depth and to get rid of textbooks. We present a sequence of contents that begins in the prime and compound numbers, discusses the meanings of multiples, divisors (and the remainders of divisions) and divisibility rules. To develop the Modular Arithmetic theme we are still exploring the definitions of Diophantine Equations. We conclude by showing the applicability of the theme to the study of Cryptography (Caesar cipher and RSA method). The work still brings results of the application of the project carried out with a specific group of students in a private school in the state of Goiás.